Population policy and reproduction in Singapore : making future citizens - Sun, Shirley Hsiao-Li. (Milton Park, Abingdon, Oxon : Routledge, 2012)
'Using the case study of Singapore, this book examines the relationship between population policies and individual reproductive decisions in low fertility contexts. It demonstrates that the effectiveness of population policy is a function of globalization processes, competing notions of citizenship, and the gap between seemingly neutral policy incentives and the perceived and experienced disparate effects. Drawing on a number of personal interviews and focus groups, the book analyses the developmental welfare state's overarching emphasis of citizen-responsibility, coupled with population policies that reinforce social inequalities and ignore social diversities, and undermine elaborate state policy efforts in encouraging citizens' biological reproduction. It goes on to discuss that in order to facilitate positive fertility decisions, the state needs to modify the economic production-at-all cost approach and pay much more attention to the increasing importance of citizen-social rights. This suggests that the Singapore government might profitably approach the phenomenon of very low fertility with major initiatives similar to those of other advanced industrialized societies.'--Publisher's description.
Introduction : making future citizens -- Low fertility and pronatalist policies -- Economic development, social investments, and population control -- Class differentiated pronatalism -- Privileging the citizen-worker -- Constructing children's multi-dimensional qualities.
Includes bibliographical references and index.
Keywords: Family policy -- Singapore; Fertility, Human -- Singapore; Singapore -- Population policy